Roles of sediment supply, geochemical composition and monsoon on organic matter burial along the longitudinal mud belt in the East China Sea in modern times. (15th July 2021) - Wang, Huawei; Kandasamy, Selvaraj; Liu, Qianqian; Lin, Baozhi; Lou, Jiann-Yuh; Veeran, Yoganandan; Lei, Huaiyan; Liu, Zhifei; Arthur Chen, Chen-Tung
Abstract: Terrestrial sediment supply and its composition, aquatic productivity and coastal hydrodynamics together control the nature of organic matter (OM) that buried in ocean margins. Distinguishing their individual roles in river-dominated continental margins is challenging, but crucial for understanding (i) the regional carbon cycle in modern times and (ii) the OM burial-climate link on shorter timescales. Here we investigate the contents of total organic carbon (TOC) and total nitrogen (TN) and stable carbon isotopic composition of TOC (δ 13 C), along with grain size and calcium carbonate, in three short, 210 Pb- and 137 Cs-dated, sediment cores (DH1-1, DH3-3 and DH5-1) from the Yangtze distal mud belt in the East China Sea to delineate the spatiotemporal distribution, origin and burial flux of sedimentary OM for the last ca. 130 years. We also use selected inorganic elements (Si, Al, Ca, Na, K, Rb and Sr) and geochemical proxies derived from them (i.e. chemical index of alteration-CIA, molar Al/Si, molar K/Na, K/Rb and Rb/Sr) to elucidate the importance of detrital composition and chemical weathering on the supply, transport and burial of OM. Bulk organic geochemical and grain size data suggest a longer transport of fine sediments-laden OM, indicating the role of China Coastal Current on hydrodynamic sorting in the study area. Spatial distribution of Al/Si, K/Na, Rb/Sr and CIA in all cores corroborates the selective transport of fine-grained minerals from the Yangtze estuary to the distal mud belt. Less variable molar C/N ratios (5.6–7.7) and δ 13 C values (–22.4 to –21.2‰) in our cores and the results of δ 13 C mixing model indicate the predominance of marine OM burial over the last century in the study area. Relationships of TOC, δ 13 C and mean grain size and spatial evolution of δ 13 C along the river-mud belt continuum show that adsorption of marine OM on the Yangtze-derived fine sediments during their southward transport. Estimated mean burial fluxes of terrestrial and marine OC (0.73 ± 0.21 and 1.88 ± 0.29 Tg C yr −1 ) indicate that the Yangtze distal mud belt, despite covering 18% of the shelf area, acts as a key OM sequestration center (>50%) in the East China Sea. Comparison of records of riverine OC burial and geochemical weathering and grain size proxies of our cores with East Asian winter monsoon index, and sediment and water discharges in the Yangtze River confirms that hydrodynamics associated with the winter monsoon winds-driven China Coastal Current predominantly controlled the sediment accumulation and OM burial along the mud belt before 1970s. Nonetheless, human activities especially the construction of Three Gorges Dam have reduced the burial flux of terrestrial OC from 0.93 to 0.54 Tg yr −1, significantly affecting the supply and burial of OM and thus the regional carbon cycle since 1970s.